2014
DOI: 10.1093/jac/dku380
|View full text |Cite
|
Sign up to set email alerts
|

Expression of homologous RND efflux pump genes is dependent upon AcrB expression: implications for efflux and virulence inhibitor design

Abstract: ObjectivesEnterobacteriaceae have multiple efflux pumps that confer intrinsic resistance to antibiotics. AcrB mediates clinically relevant multidrug resistance and is required for virulence and biofilm formation, making it an attractive target for the design of inhibitors. The aim of this study was to assess the viability of single transporters as a target for efflux inhibition using Salmonella Typhimurium as the model pathogen.MethodsThe expression of resistance–nodulation–division (RND) efflux pump genes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 52 publications
4
75
0
Order By: Relevance
“…A recent study also showed that the expression level of the acrB, acrD, and/or acrF gene was increased when one or multiple acr genes were deleted (629), and this observation was similar to the situation found among the Mex pump genes of P. aeruginosa (628). However, the compensatory acr expression level changes appeared to have only a minimal impact on the drug susceptibility phenotype (except some aminoglycosides) (629).…”
Section: Salmonella Efflux Pumpsmentioning
confidence: 55%
See 2 more Smart Citations
“…A recent study also showed that the expression level of the acrB, acrD, and/or acrF gene was increased when one or multiple acr genes were deleted (629), and this observation was similar to the situation found among the Mex pump genes of P. aeruginosa (628). However, the compensatory acr expression level changes appeared to have only a minimal impact on the drug susceptibility phenotype (except some aminoglycosides) (629).…”
Section: Salmonella Efflux Pumpsmentioning
confidence: 55%
“…In B. thailandensis, multidrug-resistant mutants selected by doxycycline overproduced AmrAB-OprA and BpeEF-OprC. When either of these pumps was inactivated, a third pump, BpeAB-OprB, was hyperexpressed, indicating the interplay among the three RND pumps (627), similar to those observed in P. aeruginosa (628) and Salmonella (629). Interestingly, an antagonistic effect between PA␤N (at 50 and 200 g/ml) and aminoglycosides/␤-lactams was observed, and the speculation was that PA␤N might have induced the overproduction of the AmrAB-OprA and BpeAB-OprB pumps (627).…”
Section: Burkholderia Sppmentioning
confidence: 76%
See 1 more Smart Citation
“…In Gram-negative bacteria, AcrR regulators control expression of efflux pumps belonging to the AcrB family, which are often encoded by divergently transcribed genes, as with acrR-acrABC in E. coli (40) and the orthologous mtrR-mtrCDE arrangement in Neisseria gonorrhoeae (41). Similarly, farE is divergently transcribed from farR and encodes an 822-amino-acid protein that is annotated as a drug exporter of the resistance-nodulation-division (RND) superfamily (30), to which AcrB and orthologous efflux pumps are also assigned (42). Genome annotation also assigns FarE to the MMPL (mycobacterial membrane proteins, large) family of proteins, on the basis of homology to large membrane proteins of Mycobacterium tuberculosis that transport mycolic acids to the cell surface (43).…”
Section: Resultsmentioning
confidence: 99%
“…The role of RND efflux pumps is not limited to the multidrug resistance (MDR) phenotype, since some of them have been shown to be required for virulence traits of different Gram-negative pathogens (11,12). This explains why AcrB is considered the main clinically relevant RND system and constitutes a privileged target for the development of efflux pump inhibitor (EPI) molecules that could be used to treat infections (13)(14)(15). In Enterobacteriaceae, numerous other genes encoding RND pumps are present in the genomes, but their roles have been poorly investigated so far.…”
mentioning
confidence: 99%